MRE11 and H2AX biomarkers in the response to low-dose exposure: balance between individual susceptibility to radiosensitivity and to genomic instability. (13th December 2011) - Colin, C.; Granzotto, A.; Devic, C.; Massart, C.; Viau, M.; Vogin, G.; Maalouf, M.; Joubert, A.; Foray, N.
Unrepaired and misrepaired DNA Double-Strand Breaks (DSBs) were shown to be the key events of radiation-induced toxicity (radiosensitivity) and genomic instability (cancer proneness), respectively. We have previously shown that immunofluorescence with γ -H2AX and MRE11 biomarkers may account for unrepaired and misrepaired DSBs for doses higher than 1 Gy. Three radiosensitivity groups had been defined (group I: radioresistance; group II: moderate radiosensitivity and cancer proneness; group III: hyper-radiosensitivity). Here, we investigated X-ray doses ranging from 9 mGy to 2 Gy in three cell lines representative of these radiosensitivity groups. We observed a non-linear dose-dependent increase of the severity of DSB, suggesting a correlation with the phenomenon of hyper-radiosensitivity to low dose; a non-linear dose-dependent increase of MRE11 foci, revealing a dose-threshold for the radiation-induced genomic instability. Altogether, these data document the evidence of a threshold in low-dose response and strongly suggest the impact of individual factor.